THE USE OF MIND MAPPING METHOD IN TEACHING WRITING OF SENIOR HIGH SCHOOL STUDENTS IN GOWA - Walay, Melisa; Yahrif, Muhammad; Sujarwo (Kumpulan Artikel Pendidikan Anak Bangsa (Kapasa) : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
The aim of this study was to determine the effectiveness of using the mind mapping method on students' skill to write English texts. This research was a quasi-experimental study with a design using two groups pretest and posttest. There were an experimental class and a control class which were given a pre-test and a post-test. The sample for this research was 72 class X students of SMAN 14 Gawa for the 2022/2023 academic year. The research instrument was a written test The tests were given as a pre-test and post-test in the experimental and control classes to assess students English writing in the pre-test and post-test The research used a scoring rubric, namely an analytical score. This research showed that mean score of pre-test was 59.06 which indicated that the students skill in the pre-test was still very low while the mean score of post-test was 73.86 which indicated that the students writing skill enough improve in the experimental class. The results of the data were analyzed using an independent sample T-test, showing that Sig.(2-tailed) was 0.000 which was lower than 0.05 so that the alternative hypothesis (H.) was accepted and the null hypothesis (Ho) was rejected the researcher proved that there was an improving of students writing skill through the mind mapping method in teaching writing. The conchision is that the use of the mind mapping method in teaching writing can improve students' skill to write English texts.